Development of optimised model for polyethylene infrastructure monitoring using mobile laser scanning technique - Al-Hader, Mahmoud Fawzi (2011)
The daily infrastructure networks’ updates are very huge due to frequent new installations, replacements and enforcements which are subject to maintenance and operation on a frequent basis. The efficiency of the maintenance and operation workflow is strongly related to the geographical location of these infrastructure networks. Due to the huge daily updates of the infrastructure networks, the ability of collecting the updated locations using the current geospatial monitoring techniques is very difficult. This research brought forward a more efficient geospatial data updating technique for the infrastructure networks. The monitoring is needed to geospatially locate and update the physical infrastructure development which significantly enhances the performance of managing and maintaining the infrastructure assets. The research concentrates on the polyethylene infrastructure materials, where power, water and communication networks are either covered or protected by polyethylene materials. The research conducted a technical comparison between the current geospatial data collection techniques and developed an overall performance evaluation in the sense of coverage capacity, objects extraction, data formats, time initialization of the systems and post processing time consumption. The use of mobile laser scanning technology had achieved the best evaluation performance. The evaluations were based on conducting a detailed data analysis, data collection, modelling and interpretation. Prior conducting the performance evaluation, the research investigates the mobile laser behaviour and recognition capabilities with respect to polyethylene infrastructure materials. Each material has different characteristics and accordingly has a different response (reflections and absorptions) to laser pulses, where this response is constant and only material dependent. The mobile laser pulses response constant for the polyethylene infrastructure materials has been concluded after analysing the pulses behaviour and its correlations with the mission ground speed and exposed scanned surface. The obtained mobile laser scanning constant for the polyethylene infrastructure material is 726 pulses/cm when the system ground speed is 16.49 km/h. The concluded mobile laser pulses constant were used to develop a mathematical method for re-planning the mobile laser scanning missions to obtain the best model for updating the polyethylene infrastructure networks. Mobile laser scanning using the improved planning missions can detect 97% of the polyethylene infrastructure networks in a very good performance.